Electroencephalographic findings among inpatients with COVID-19 in a tertiary hospital from a middle-income country - Luíza Alves CORAZZA; João Fellipe Santos TATSCH; Maraysa Pereira BARROS; Apolônio Peixoto de QUEIROZ; Luana Lôbo Ribeiro BATISTA; Mariana Barbosa AIDAR; Meire Argentoni BALDOCCHI; Maria Sheila Guimarães ROCHA; Sonia Maria Dozzi BRUCKI (Arquivos de Neuro-Psiquiatria)
ABSTRACT Background: In 2019, the world witnessed the emergence of a new type of coronavirus - the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The spectrum of coronavirus disease 2019 (COVID-19) is variable, and amongst its manifestations are neurological implications. Objective: This report aimed to describe electroencephalographic findings in COVID-19 patients from a general tertiary hospital in São Paulo, Brazil. Methods: It was a retrospective, observational, and non-interventional study. Data were collected anonymously, comprising inpatients from Mar 1 to Jun 30, 2020, either confirmed (positive RT-PCR) or probable cases (CO-RADS 4/5) who had performed EEG during hospitalization. Results: Twenty-eight patients were enrolled, 17 (60.7%) women and 11 men, with a median age of 58 (minimum and maximum: 18-86; IQR 23.5). COVID-19 diagnosis was confirmed in 22 (78.5%). Twenty-one patients (75%) had severe disease, requiring mechanical ventilation due to acute respiratory distress syndrome (ARDS); 16 (57.1%) patients developed adjunct sepsis throughout hospitalization. There was no specific pattern found for COVID-19 in EEG. No patients presented with status epilepticus or electrographic events; most patients developed an encephalopathic pattern, as seen in most studies, with a high prevalence of altered mental status as an indication for EEG. Adjunct sepsis was associated with higher mortality. Conclusions: EEG presents as a useful tool in the context of COVID-19, as in other conditions, to differentiate nonconvulsive status epilepticus (NCSE) from encephalopathy and other causes of mental status alterations. Further studies are required to analyze whether there might be a specific EEG pattern to the disease.